(untitled) (Eurasian Scientific Herald, 2022)
In the article the results of the research on teaching foreign language to preventive medicine specialists (hygienists-epidemiologists) have been discussed. The results of scientific-methodological research and experimental works on the organization foreign language teaching through differentiated-continuous and professionally orientied principle and formation of professional communicative competence of medical students in foreign languages were presented. The experiments on developing professional communicative competence in a foreign language were carried out at Andijan state medical institute, Tashkent medical academy, Fergana branch of Tashkent medical academy. The factors influencing on language learning, communicative skiils and motivation of the students in Experiment and Control groups in medical higher school were assessed by students themselves and the results were analyzed